The Aesthetics and Religiosity of Artworks in the Renaissance： Dürer's The Four Apostles as an Example - Zhao, Ruzan (Transactions on Social Science, Education and Humanities Research, 2024)
Dürer was the most representative painter of the German Renaissance. He was born, lived, painted, and died in his hometown of Nuremberg. He was deeply influenced by the Protestant movement and responded to the changing times through artistic expression. when Nuremberg formally converted to Protestantism in March 1525, Dürer did not follow the trend but presented one of his paintings, The Four Apostles, to the city in 1526, which expressed his longing for a secular government and his hope that it would lead the people back to a harmonious and stable life. Focusing on Renaissance Germany, this study takes into account the influence of the German Reformation and the Peasants' War and examines Dürer's interaction with the social environment. The study employs documentary analysis to find and read relevant information and literature, and visual analysis to interpret The Four Apostles in detail. The advantage of these methods is that they can well analyse the social environment in which the art was created, as well as understand the inner psychology of the painter when he created the art. The ultimate goal of this study is to better understand the inextricable relationship between Renaissance aesthetics and religious beliefs.